Legal Protection Of Workers Without Company Guarantees Due To The Pandemic Based On Legal Certainty - Raharja, Gan gan Gunawan (Fakultas Hukum, Universitas Islam Bandung, 2023)
ABSTRACT This research is normative legal research, the collection of legal materials is done by identifying and inventorying literature or secondary data, which includes primary, secondary and tertiary legal materials. The results of the study show how the rights of workers who were laid off due to the Covid 19 pandemic at the Ramayana City Plaza Depok Store, and legal remedies for workers who were laid off. First, workers' rights in employment relations. The most basic rights are normative rights, namely rights that have been regulated in the Law and the Principle of Legal Certainty. Normative rights can be in the form of financial (money) and non-financial rights. In the event of termination of employment/ layoffs, the employer is required to pay severance pay and/or service gratuity and compensation pay that should have been received by the worker. Second, legal remedies that can be taken by workers, workers can carry out deliberations or through industrial relations dispute resolution procedures outside the court, based on the principle of legal certainty which is based on Law No. 13 of 2003 concerning Manpower. From the results of this study it can be concluded that the employment relationship is a relationship that arises between workers and employers after a previous agreement was made by the parties concerned. This working relationship will bring rights and obligations between employers and workers. Legal remedies that can be taken if the above rights cannot be obtained by workers, then workers can carry out deliberations or through industrial relations dispute resolution procedures outside the court, based on Law No. 13 of 2003 concerning Manpower and the Principle of Legal Certainty, legal remedies through bipartite , conciliation, arbitration or mediation. And if negotiations/deliberations do not reach an agreement, then the final step is to go through the industrial relations court.Keywords: Layoffs, Retail Industry ABSTRAKPenelitian ini merupakan penelitian hukum normatif, pengumpulan bahan hukum dilakukan dengan prosedur identifikasi dan inventarisasi bahan pustaka atau data sekunder, yang mencakup bahan hukum primer, sekunder dan tersier. Hasil penelitian menunjukkan bagaimana hak hak pekerja yangdi PHK akibat pandemi covid 19 di di Store Ramayana City Plaza Depok, dan upaya hukum terhadap pekerja yang di PHK. Pertama hak pekerja dalam hubungan kerja. Hak yang paling mendasar adalah hak-hak normatif, yaitu hak-hak yang telah diatur dalam Undang-Undang dan Asas Kepastian Hukum . Hak-hak normatif dapat berupa hak-hak yang menyangkut finansial (uang) dan nonfinansial. Bila terjadi pemutusan hubungan kerja/PHK, pengusaha diwajibkan membayar uang pesangon dan atau uang penghargaan masakerja dan uang penggantian hak yang seharusnya diterima pekerja. Kedua, upaya hukum yang dapat dilakukan oleh pekerja, maka pekerja dapat melakukan musyawarah atau melalui prosedur penyelesaian perselisihan hubungan industrial di luar pengadilan, berdasarkan Asas kepastian hukum yang berlandaskan peraturan Undang-Undang No 13 Tahun 2003 tentang Ketenaga kerjaan. Dari hasil penelitian ini dapat disimpulkan bahwa hubungan kerja merupakan suatu hubungan yang timbul antara pekerja dan pengusaha setelah diadakan perjanjian sebelumnya oleh pihak yang bersangkutan. Dengan hubungan kerja tersebut akan membawa hak dan kewajiban antara pengusaha dan pekerja. Upaya Hukum yang dapat dilakukan apabila hak diatas tidak dapat diperoleh oleh pekerja, maka pekerja dapat melakukan musyawarah atau melalui prosedur penyelesaian perselisihan hubungan industrial di luar pengadilan, berdasarkan Undang-Undang No 13 Tahun 2003 tentang Ketenaga kerjaan dan Asas Kepastian Hukum, upaya hukum melalui bipartit, konsiliasi, arbitase atau mediasi. Dan jika dengan cara perundingan/ musyawarah tidak mencapai kesepakatan, maka langkah terakhir adalah melalui pengadilan hubungan industrial. Kata Kunci : PHK, Industri Ritel